2015
DOI: 10.2528/pierl15061501
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity Relations for Nonlinear Galvanomagnetic Transducer

Abstract: Abstract-This paper deals with reciprocity relations derivation for a nonlinear, stationary, homogeneous and isotropic plasma-like medium in an external homogeneous magnetic field. A special case of such a medium is the charge carriers collective in semiconductors. It is shown that the classical reciprocity relations will be valid even in the presence of nonlinearity, and they can be used for Hall magnetometer bias compensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The values of functions were averaged for every value of current in 10 measurings. The obtained dependences were approximated by fourth-order polynomials according to expression (5), and the linear functions (8) were built. We find that increasing polynomials degree has no influence on the accuracy of function estimation for our experimental data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of functions were averaged for every value of current in 10 measurings. The obtained dependences were approximated by fourth-order polynomials according to expression (5), and the linear functions (8) were built. We find that increasing polynomials degree has no influence on the accuracy of function estimation for our experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical analysis has shown that for any homogeneous, stationary and isotropic medium which is in the external magnetic field ofB e , classic reciprocal relations must be valid even at the presence of non-linearity [5] and in inhomogeneous field [6]. Both theoretical reasonings and partial results require experimental verification in more general conditions.…”
Section: Introductionmentioning
confidence: 99%